BIM-Sim: Interactive Simulation of Broadband Imaging Using Mie Theory - Berisha, Sebastian; van Dijk, Thomas; Bhargava, Rohit; Carney, P. Scott; Mayerich, David (Frontiers in Physics, 2017)
Understanding the structure of a scattered electromagnetic (EM) field is critical to improving the imaging process. Mechanisms such as diffraction, scattering, and interference affect an image, limiting the resolution and potentially introducing artifacts. Simulation and visualization of scattered fields thus plays an important role in imaging science. However, the calculation of scattered fields is extremely time-consuming on desktop systems and computationally challenging on task-parallel systems such as supercomputers and cluster systems. In addition, EM fields are high-dimensional, making them difficult to visualize. In this paper, we present a framework for interactively computing and visualizing EM fields scattered by micro and nano-particles. Our software uses graphics hardware for evaluating the field both inside and outside of these particles. We then use Monte-Carlo sampling to reconstruct and visualize the three-dimensional structure of the field, spectral profiles at individual points, the structure of the field at the surface of the particle, and the resulting image produced by an optical system.